Asymmetry of cerebral microbleeds and superficial siderosis in cerebral amyloid angiopathy. Issue 5 (8th May 2017) - Sharma, Rohit; McKenzie, Dean; Dearaugo, Stephanie; Infeld, Bernard; O'Sullivan, Richard; Gerraty, Richard P
Abstract : Objectives: Susceptibility-weighted imaging (SWI) MRI in cerebral amyloid angiopathy (CAA) can detect hemosiderin-laden lobar cerebral microbleeds (CMBs) and cortical superficial siderosis (cSS). To assess the asymmetry of CMBs and cSS across cerebral hemispheres in patients with CAA, we performed a single-centre retrospective study of patients in whom SWI had been performed and who met the modified Boston criteria for 'probable CAA'. 1 Methods: Clinical and MRI data from a five-year period in patients with either CAA, a haemorrhage potentially caused by CAA or clinical symptoms mimicking CAA. Patients were excluded who did not have SWI, did not meet the modified Boston criteria diagnosis for 'probable CAA', or had a clear indication of another cause for haemorrhage. 'Asymmetry' was defined as a cerebral hemisphere having two-thirds or more of the total CMB or cSS burden. Results: From 734 patients reviewed, 59 were available for analysis, including six with two SWI scans. The majority of patients demonstrated asymmetrical SWI findings. In patients with lobar CMBs (n=58), the distribution of lobar CMBs was asymmetrical in 40 patients (68.9%), including 19 patients (32.8%) who had lobar CMBs confined to one hemisphere only. In patients with cSS (n=27), the distribution of cSS was asymmetrical in 18 patients (66.7%), including 13 patients (48.1%) who had cSS affecting sulci in only one hemisphere. In exploratory analysis of patients with two SWI scans, all patients demonstrated an increase in CMB and cSS counts between scans, including multiple instances of new lesions appearing in close proximity to older lesions. Conclusions: SWI abnormalities in CAA have striking asymmetry in many patients. This may result from non-uniform development and progression of CAA throughout the brain, and is consistent with the recent proposition of beta-amyloid proteins 'seeding' and 'spreading' along vessels. 2